2013
DOI: 10.1111/jam.12268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus rhamnosus on asthma with an adoptive transfer of dendritic cells in mice

Abstract: Aim: This study was designed to investigate whether the protective effects of Lactobacillus rhamnosus (Lcr35) on allergic asthma are associated with the adoptive transfer of dendritic cells (DCs) and regulatory T cells (Tregs), using a mouse experimental model of asthma. Methods and Results: BALB/c mice were orally administered Lcr35 or intravenously treated with in vivo Lcr35-treated DCs daily and were then sensitized and challenged with ovalbumin (OVA) in accordance with a model of asthma protocol. Both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…In addition, some studies have shown this effect only in tumors19). Our research confirms that DCs are involved in the suppression of asthma by probiotics following the transfer of mature DCs in mice56).…”
Section: Immunological Mechanisms Involved In the Effects Of Probiotisupporting
confidence: 85%
“…In addition, some studies have shown this effect only in tumors19). Our research confirms that DCs are involved in the suppression of asthma by probiotics following the transfer of mature DCs in mice56).…”
Section: Immunological Mechanisms Involved In the Effects Of Probiotisupporting
confidence: 85%
“…The findings of this study are concordance with those reported in other recent studies (Kim et al . , ) and provide additional support for the preventive effects of LCR35 against allergic disease.…”
Section: Discussionmentioning
confidence: 90%
“…Tregs are known to modulate the upregulation of Th1 and Th2, thereby inhibiting the progression of inflammation in allergic conditions (24). Many studies have suggested the involvement of Tregs in controlling various aspects of AD (2527). Ingested probiotics are recognized by pattern recognition receptors, such as TLRs on DCs (28), that are essential for immunological homeostasis in the gut and that play an important role in allergic diseases; therefore, CD4 + Foxp3 + Tregs are increased in MLNs (10, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested the involvement of Tregs in controlling various aspects of AD (2527). Ingested probiotics are recognized by pattern recognition receptors, such as TLRs on DCs (28), that are essential for immunological homeostasis in the gut and that play an important role in allergic diseases; therefore, CD4 + Foxp3 + Tregs are increased in MLNs (10, 27). In this study, analysis of Tregs in MLNs by using flow cytometry showed that the percentage of CD4 + Foxp3 + Tregs increased significantly in the GI7-H group compared with that of the control group, whereas no changes were observed in the control and GI7-L groups (Fig.…”
Section: Discussionmentioning
confidence: 99%